The integration of virtues in the novel “The Palace Facing The Sea” (Istana Menghadap Laut) by Nazri Hussein according to Malaysian Malaysian National Education Philosophy (1987) - Roslan, Nur Maisarah; Subramaniam, Vijayaletchumy; Redzuan Abdullah, Muhammad Alif (Human Resource Management Academic Research Society, 2023)
Virtues are traits and attitudes that can be cultivated through teaching and learning that every person needs to have in communicating with each other. The nature of pure values should be within every human being so that they can think and act well and not make mistakes or do things that are not right for others. Due to the importance of pure value in every person, it is also taught in school and placed in the delivery of a story through the writing of a novel that can be applied to the readers. Therefore, the objective of this study is to identify and discuss the application of pure values in the novel The Palace Facing the Sea (Istana Menghadap Laut) by Nazri Hussein according to the Malaysian National Education Philosophy (1987). This study uses the qualitative method in analyzing the data and the data obtained is through the novel The Palace Facing the Sea (Istana Menghadap Laut) by Nazri Hussein. The data analysis uses the document analysis method where the data is taken from the filling of the novel and formulated according to the relevant objectives. The data analyzed is based on the (Malaysian National Education Philosophy, 1987). The study results found that the importance of pure values in novel writing is very high. This is because the nature of pure values should be cultivated for everyone. The nature of pure values is also very important and must be present in every novel writing because it can greatly impact readers. The application of pure values should be expanded in various ways so that they can be communicated to the public in a widespread and attractive manner.